A Preliminary Inventory and Assessment of Uranium Resources in Mine Wastes - IAEA (IAEA, 2021)
Typically, discussions of the uranium production cycle are focused on either the economic extraction of resources, or on the environmental and remediation aspects as parallel aspects in a linear cradle-to-grave process. In this publication, resource evaluation is expanded to the full life of the mine to include evaluation of resources in residual waste products. This is viewed in the context of potential reuse or remining of so-called anthropogenic resources in a circular economy. The publication is intended to not only provide a preliminary inventory of uranium contained in mine wastes including the desirable goal of comprehensive extraction in the (uranium) mining industry, but also to provide an initial framework to integrate this aim with those of environmental and remediation considerations in achieving zero waste.
Description based upon print version of record.
Keywords: Metal wastes.; Uranium mines and mining.; Radioactive wastes.; elektronické knihy; electronic books